Prevalence, Surgical Management, and Audiologic Impact of Sigmoid Sinus Dehiscence Causing Pulsatile Tinnitus. Issue 1 (January 2021) - Ettyreddy, Abhinav R.; Shew, Matthew A.; Durakovic, Nedim; Chole, Richard A.; Herzog, Jacques; Buchman, Craig A.; Wick, Cameron C.
Abstract : Objective: To evaluate the prevalence, surgical management, and audiologic impact of pulsatile tinnitus caused by sigmoid sinus dehiscence. Study Design and Setting: Retrospective chart review at a tertiary care hospital. Patients: Adults with unilateral pulsatile tinnitus attributable to sigmoid sinus dehiscence who underwent resurfacing between January 2010 and January 2020. Interventions: Transmastoid sigmoid resurfacing. Main Outcome Measures: Resolution of pulsatile tinnitus; audiologic outcomes; complications; tinnitus etiologies. Results: Nineteen patients (89.4% women) had surgery for suspected sigmoid sinus dehiscence. The mean dehiscence size was 6.1 mm (range, 1–10.7 mm). Eight patients had concurrent sigmoid sinus diverticulum and one patient also had jugular bulb dehiscence. Only two patients (10.5%) had the defect identified by radiology. Low-frequency pure-tone average, measured at frequencies of 250 and 500 Hz, showed a significant median improvement of 8.8 dB following resurfacing (18.8 dB versus 10.0 dB, p = 0.02). The majority of patients had complete resolution of pulsatile tinnitus (16/19, 84.2%). Of those without complete resolution, two patients had partial response and one patient had no improvement. There were no significant complications. Of 41 consecutively tracked patients with a pulsatile tinnitus chief complaint, sigmoid pathology represented 32% of cases. Conclusions: Sigmoid sinus dehiscence represents a common vascular cause of pulsatile tinnitus that, if properly assessed, may be amenable to surgical intervention. Sigmoid sinus resurfacing is safe, does not require decompression, and may improve low-frequency hearing. Radiographic findings of dehiscence are often overlooked without a high index of clinical suspicion. Its relationship with transverse sinus pathology and idiopathic intracranial hypertension remain unclear.